Reformas a la Ley de Gestion Ambiental respecto al incumplimiento de las normas de protección ambiental - Mina Achilie, Lennin Ever (2015)
One issue that has gained interest in the last decade in the environmental legal system is the establishment of actions to repair the damage committed against nature. The social phenomenon of conscious or unconscious destroy our habitat has helped generated in our country laws to control and regulation but there is a weak enforcement in the Ecuadorian environmental legislation which has given rise to specific instances of environmental damage have left without being sanctioned by the competent authorities. With the force of the current Constitution of the Republic is constitutionally established that responsibility in managing nature is the state, however, the Constitution establishes the right to seek indemnity, therefore, the responsibility lies with all institutions of and overall public sector is the responsibility of all citizens who live in Ecuador. In terms of nature, it is the first time in all constitutions that have attended, the current Constitution of the Republic of Ecuador, in Article 10, point: "Nature will be subject to those rights that recognize the Constitution". and to supplement these inherent rights of human beings, says: Art. 14 "Rights of the population to live in a healthy and ecologically balanced environment ...". Similarly in Article 71 provides: "Nature or Pachamama, where it is reproduced and life, has the right to be fully respects their existence and maintenance and regeneration of its vital cycles, structure, functions and evolutionary processes ". . Also in the Art 72 states: "Nature has the right to restoration. This restoration is independent of the obligation of the State and natural or legal persons for compensation to individuals and groups who depend on affected natural systems". Regarding environmental damage Environmental Management Act in Chapter II establishes the Administrative Litigation and Administrative Actions. While it is true that the principle of administrative liability is founded on prevention, there are ways in which the administration acts in a precautionary and restorative. That is, within the system of administrative liability may be imposed in unison sanctions such as fines, closure, and also provide repair environmental damage while you are supposed breach of a duty. One of the mechanisms used administrative penalty for excellence in the country has been to impose fines for breaches of the rule, without necessarily the resources collected by those sanctions are employed in repairing the damage. Article 46 of the Environmental Management Act states that "When individuals, by act or omission contravening the rules of environmental protection, the competent authority shall, without prejudice to the penalties provided in this Act, the following administrative measures: ) Forfeiture of species of flora and fauna obtained illegally and devices used to commit the offense; and, b) Require the regularization of authorizations, permits, studies and evaluations; and verify compliance with measures to mitigate and compensate for environmental damage, within a period of thirty days". This type of repair, despite its importance, is very limited because it is usually applied to the activities of lower environmental or sectoral relevance such as the oil sector, though activities such as forestry mining or even have global impacts, are not evaluated in a timely manner, and the penalties provided repair fail to generate unprecedented for non-repetition. It is therefore necessary to amend the Law on Environmental Management to adapt formally and materially rights and principles enshrined in the Constitution incorporating sanctions commensurate to the damage caused to the environment that offenders are punished in order to avoid the recurrence of this type violations and made aware people about the importance of the environment